A provincial adaptation of clinical practice guidelines for depression in primary care: a case illustration of the ADAPTE method. Issue 6 (17th June 2015) - Roberge, Pasquale; Fournier, Louise; Brouillet, Hélène; Delorme, André; Beaucage, Clément; Côté, Rodrigue; Demers, Pierre; Gervais, Michel; Laflamme, France; Latulippe, Louise; Marchand, André; Patry, Simon; et al.
Abstract: Rationale, aims and objectives: Mental health services for patients with a major depressive disorder are commonly delivered by primary care. To support the uptake of clinical practice guidelines in primary care, we developed and disseminated a practice protocol for depression tailored for a multidisciplinary audience of primary mental health care providers with the ADAPTE methodology. The research questions addressed in this study aimed at examining the experience of the development process of a mental health practice protocol in terms of adaptation, facilitation and implementation. Methods: We present a descriptive case study of the development and implementation of a practice protocol for major depressive disorder for primary mental health care in the organizational and cultural context of the province of Québec (Canada), following the steps of the ADAPTE methodology. An expert committee composed of general practitioners, mental health specialists, health care administrators and decision makers at regional and provincial levels participated in the protocol development process. Results: The practice protocol was based on two clinical practice guidelines: the NICE guideline on the treatment and management of depression in adults (2009, 2010) and the Canadian Network for Mood and Anxiety Treatments clinical guidelines for the management of major depressive disorder in adults (2009). A stepped care model was embedded in the protocol to facilitate the implementation of clinical recommendations in primary mental health care. A multifaceted dissemination strategy was used to support the uptake of the protocol recommendations in clinical practice. Conclusions: The ADAPTE methodology provided structure, rigour and efficiency to the trans‐contextual adaptation of guideline recommendations. We will share the challenges associated with the adaptation of clinical recommendations and organizational strategies for a mental health guideline, and the dissemination of the practice protocol in primary care.